Seasonal Features and a Case Study of Tropopause Folds over the Tibetan Plateau - Jiali Luo; Wenjun Liang; Pingping Xu; Haiyang Xue; Min Zhang; Lin Shang; Hongying Tian (Advances in Meteorology)
Tropopause fold is the primary mechanism for stratosphere-troposphere exchange (STE) at the midlatitudes. Investigation of the features of tropopause folds over the Tibetan Plateau (TP) is important since the TP is a hotspot in global STE. In this study, we investigated seasonal features of the tropopause fold events over the TP using the 40-year ERA-Interim reanalysis data. The development of a tropopause folding case is specifically examined. The results show that shallow tropopause folds occur mostly in spring, while medium and deep folds occur mostly in winter. The multiyear mean monthly frequency of shallow tropopause folds over the TP reaches its maximum value of about 7% in May and then decreases gradually to its minimum value of 1% in August and increases again since September. Deep folds rarely occur in summer and autumn. Both the seasonal cycle and seasonal distribution of total tropopause folds over the TP are dominated by shallow folds. The relative high-frequency areas of medium and deep folds are located over the southern edge of the TP. The westerly jet movement controls the displacement of the high-frequency folding region over the TP. The region of high-frequency tropopause folds is located in the southern portion of the plateau in spring and moves northward in summer. The jet migrates back to the south in autumn and is located along about 30°N in winter, and the region where folds occur most frequently also shifts southward correspondingly. A medium fold event that occurred on 29 December 2018 is used to demonstrate the evolution of a tropopause fold case over the TP in winter; that is, the folding structure moves from west to east, the tropopause pressure is greater than 320 hPa over the folding region, while it is about 200 hPa in the surrounding areas, and the stratospheric air with high potential vorticity (PV) is transported from the high latitudes to the plateau by meridional winds. A trajectory model result verifies the transport pathway of the air parcels during the intrusion event.